Spondylocostal dysplasia: a rare cause of respiratory distress in term neonates - Bhargava, Anshul; Susnerwala, Sukena J.; Kaur, Samandeep; Krishna, Akshaya (International Journal of Contemporary Pediatrics, 2022)
Jarcho-Levin syndrome (JLS) also known as spondylocostal dysplasia is a rare congenital dysplastic disorder involving ribs and vertebrae. It as an autosomal recessive form of inheritance however dominant forms have also been reported. Multiple genes have been postulated to be causative, however exact genetic basis is not known. Infants usually present at birth with respiratory distress and have varying degree of thoracic and vertebral anomalies. We present a case of term male infant with a clinical diagnosis of JLS. The infant presented at birth with distress with no significant antenatal risk factors. On examination he was found to have a short neck, short trunk, accessory nipple with asymmetrical chest wall. X-ray suggested absent ribs (2-8) on left side with hemivertebrae (T3-T8). The baby was managed conservatively and is being followed up with neonatologists, orthopaedicians and pediatric surgeons.